2006
DOI: 10.1128/aem.72.1.638-644.2006
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Nitrous Oxide Production from Nitrification and Denitrification on the Basis of Isotopomer Abundances

Abstract: The intramolecular distribution of nitrogen isotopes in N 2 O is an emerging tool for defining the relative importance of microbial sources of this greenhouse gas. The application of intramolecular isotopic distributions to evaluate the origins of N 2 O, however, requires a foundation in laboratory experiments in which individual production pathways can be isolated. Here we evaluate the site preferences of N 2 O produced during hydroxylamine oxidation by ammonia oxidizers and by a methanotroph, ammonia oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
669
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(741 citation statements)
references
References 39 publications
68
669
4
Order By: Relevance
“…The two enzymes are structurally very different and show significantly different isotope fractionations on bulk (Martin and Casciotti, 2016). Sutka and Ostrom (2006) conclude that a difference in the nitrite reductase does not have an effect on the SP during denitrification. This conclusion is based on measurements of two denitrifiers (P. chlororaphis, ATCC 43928; and P. aureofaciens, ATCC 13985) possessing cd1-type nitrite reductase and Cu-containing nitrite reductase, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The two enzymes are structurally very different and show significantly different isotope fractionations on bulk (Martin and Casciotti, 2016). Sutka and Ostrom (2006) conclude that a difference in the nitrite reductase does not have an effect on the SP during denitrification. This conclusion is based on measurements of two denitrifiers (P. chlororaphis, ATCC 43928; and P. aureofaciens, ATCC 13985) possessing cd1-type nitrite reductase and Cu-containing nitrite reductase, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Applying different incubation techniques on soils with different properties showed SP during production of N 2 O between −3 and 9 ‰ and between −0.9 and −8.2 ‰ during reduction (Well and Flessa, 2009a, b;Köster et al, 2013a;Lewicka-Szczebak et al, 2014. During production of N 2 O in bacterial culture experiments (involving P. chlororaphis, ATCC 43928; P. aureofaciens, ATCC 13985; and P. denitrificans, ATCC 17741), Thompson et al (2004), Toyoda et al (2005), Sutka and Ostrom (2006), and Ostrom and Ostrom (2011) found SP values of −27.4 and 1.3 ‰ and bulk values of between −42.6 and 36.7 ‰. The wide range of bulk presented both in this study and by others confirms the difficulties in the use of bulk in N 2 O evolution analysis.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Characteristic SP values of 33‰ and 0‰ for NH 2 OH oxidation and NO 2 -reduction (nitrifier denitrification and heterotrophic bacterial denitrification), respectively, which were estimated in specific pure cultures, were used for estimation of the contribution to each process (Sutka et al, 2006). Approximate contributions of NH 2 OH oxidation and NO 2 -reduction to N 2 O production were estimated by assuming that each process is linearly proportional to the SP value using the following equation:…”
Section: Isotopomer Analysismentioning
confidence: 99%
“…Analyses of the intermolecular distributions of 15 N in N 2 O (isotopomers) are regarded as useful parameters to infer the predominant N 2 O production pathway (Wunderlin et al, 2013;Sutka et al, 2006;Toyoda et al, 2005;. Isotopomer ratios (site-specific N isotope ratios in asymmetric molecules of NNO) give us qualitative information on N 2 O production and consumption pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Site preference has emerged as a potential conservative tracer for microbial N 2 O production because 1) it is independent of the isotopologue composition of the substrates and 2) it does not exhibit changes during the course of production. Distinct site preference values for N 2 O production due to bacterial denitrification, including nitrifier denitrification, relative to hydroxylamine oxidation and fungal denitrification provide a fundamental basis that facilitates the resolution of production pathways in the natural environment (Sutka et al, 2006.…”
Section: Introductionmentioning
confidence: 99%